Fast Fading Characterization for Body Area Networks in Circular Metallic Indoor Environments - Filipe D. Cardoso; Pawel T. Kosz; Manuel M. Ferreira; Slawomir J. Ambroziak; Luis M. Correia (IEEE Access, 2020)
With the increasing development of 5G and Body Area Network based systems being implemented in unusual environments, propagation inside metallic structures is a key aspect to characterize propagation effects inside ships and other similar environments, mostly composed of metallic walls. In this paper, indoor propagation inside circular metallic structures is addressed and fast fading statistical distributions parameters are obtained from simulation, being assessed with measurements at 2.45 GHz in a passenger ferry discotheque with an 8 m diameter circular shape. It is observed that, in this kind of environments, second order reflections are particularly relevant due to the walls' high reflective nature. Globally, it is concluded that the Rayleigh distribution can be used to characterize fast fading effects with no significant loss of accuracy compared to the Rice one, since a low value of the Rice parameter is observed, being below 3.1 dB, even under Line-of-Sight conditions. Moreover, it is observed that, from the fast fading viewpoint, the best transmitter position is at the circle center.